OUTCOME AND PROGNOSTIC FACTORS OF STROKE IN CHILDREN PRESENTING AT AN ARMY HOSPITAL IN PAKISTAN: Stroke in Children - Mahmud, Shahid; ., Shahneela; Shah, Sajid Ali (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the outcome and prognostic factors of stroke in children presenting at Military Hospital Rawalpindi. Study Design: Cross-sectional study. Place and Duration of Study: This study was conducted at the department of Pediatrics, Military Hospital Rawalpindi, from Oct 2012 to Mar 2014. Patients and Methods: Sixty consecutive children presenting with stroke were included in this study after taking written informed consent from the guardians/parents. A predesigned proforma was used to record patient’s demographic details along with the presenting complaints, type of stroke, underlying cause and outcome. Results: The mean age of the patients was 3.49 ± 3.29 (Mean ± SD) years. There were 35 (58.3%) male and 25 (41.7%) female children. Ischemic stroke was the most frequent and was observed in 37 (61.7%) patients followed by hemorrhagic (16.7%), sinovenous thrombosis (8.3%) and ischemia with hemorrhagic findings (6.7%). Mixed lesions and transient ischemic attacks were reported in 2 (3.3%) patient each. Mean length of hospital stay was 9 ± 6 (Mean ± SD) days. Sixteen (26.7%) children recovered completely while 41 (68.3%) children had some neurological deficit at discharge. Mild to moderate deficit was recorded in 21 (35.0%) children while 20 (33.3%) children had severe deficit. Three (5.0%) patients expired during hospital stay. Conclusion: Ischemic stroke was the most common cause of paediatric stroke. Important risk factors of peadiatric stroke included congenital heart diseases and intracranial infections. Poor prognostic factors included male gender, age less 5 years and congenital heart disease.